Pemanfaatan Internet Oleh Mahasiswa Dalam Menghadapi Masyarakat Ekonomi ASEAN - Lilik Indrawati (Fakultas Ekonomi Universitas Katolik Darma Cendika, 2015)
The education process is basically the transfer of information. The rapid development of information technology have an impact on human life, especially education. Its positive impact is closely linked to improved quality of life. Information facing ASEAN Economic Community (AEC) is so easily obtained either through the mass media, electronics, as well as through a network of internet technology. The Internet is a network of information, communication, and various sources are not infinite number of which can be used to help users produce a final project, thesis, thesis, dissertation, project work, and so on. Internet as a tool for achieving information on a global scale. Users can now obtain more information than what is contained in the textbooks by searching and accessing all websites around the world. Especially for the students, with the internet which is easily accessible anywhere, using either WIFI or a particular provider, making it easier for students to obtain data or news from domestic and foreign news. Students may also work on assignments, tests, and develop materials that have been received in the lecture. Thus, more extensive knowledge of students.